Nutritional Pattern And Healing Of Perineum Wound On Postpartum Period - Frilasari, Heni; Saudah, Noer; Prameswari, Veryudha Eka; Azizah, Yeni Nur; Suhita, Byba Melda (Universitas STRADA Indonesia, 2020)
Background: Postpartum period was the return of uterine implants such as before pregnancy which takes 6 weeks after born. Good nutrition patterns would speed healing wound perineum. The high nutritional content of calories, protein, fluids, and vitamins needed for speed up perineal wound closure.Purpose: This study aimed to determine the relationship of postnatal maternal nutritional patterns with the healing of perineal wounds in Puri community health center Mojokerto.Methods: Analytical research design with Cross-Sectional. The population used postpartum mothers with perineal injuries. The sampling technique was through consecutive. The sample size was 90 respondents. The independent variable was nutrition pattern and the dependent variable was perineal wound healing. The instrument used was a questionnaire sheet postpartum maternal nutrition pattern and observation sheets for perineal wound healing.Results: The results showed 56 respondents (63.3%) had good nutrition patterns and good perineal wound healing, 27 respondents (30%) had poor nutrition patterns and moderate perineal wound healing, as many as 7 respondents (6.7%) had nutritional patterns less and bad perineal wound healing. Chi-Square statistical test results showed ? (0,000) <? 0.05.Conclusion: It could concluded that there was a relationship between the nutritional pattern of the puerperal mother with the healing of perineal wounds. High caloric, protein, fluid and mineral intake and vitamins in the puerperium mother will accelerate the process of new cell regeneration so that the puerperal perineal wound heals faster. Postpartum mothers are expected to maintain a nutritional pattern for healing the perineal wound and not do certain food restrictions during the puerperium